Matrix stiffness reverses the effect of actomyosin tension on cell proliferation - Mih, Justin D. (The Company of Biologists, 2012)
The stiffness of the extracellular matrix exerts powerful effects on cell proliferation and differentiation, but the mechanisms transducing matrix stiffness into cellular fate decisions remain poorly understood. Two widely reported responses to matrix stiffening are increases in actomyosin contractility and cell proliferation. To delineate their relationship, we modulated cytoskeletal tension in cells grown across a physiological range of matrix stiffnesses. On both synthetic and naturally derived soft matrices, and across a panel of cell types, we observed a striking reversal of the effect of inhibiting actomyosin contractility, switching from the attenuation of proliferation on rigid substrates to the robust promotion of proliferation on soft matrices. Inhibiting contractility on soft matrices decoupled proliferation from cytoskeletal tension and focal adhesion organization, but not from cell spread area. Our results demonstrate that matrix stiffness and actomyosin contractility converge on cell spreading in an unexpected fashion to control a key aspect of cell fate.